2010
DOI: 10.1002/lary.20858
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship in otolaryngology residency: The resident perspective

Abstract: The current study reveals variability in the mentorship experience in otolaryngology residency. Potential deficiencies may exist, including absence of formal mentorship in some residency programs. Increased attention to mentorship, especially with regard to research, career preparation, and quality of life may improve the overall residency experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…Although this measure differed significantly between our residents and those studied by Golub et al, 22 Although mentoring has been gaining attention, 23,24,36 to our knowledge, the current study is the first to quantify how many osteopathic otolaryngology residents have a Emotional exhaustion, depersonalization, and personal accomplishment were scored as subscales on the Maslach Burnout Inventory-Human Services Survey. b The depersonalization and personal accomplishment subscales could not be calculated for 1 respondent because of incomplete responses to some questions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although this measure differed significantly between our residents and those studied by Golub et al, 22 Although mentoring has been gaining attention, 23,24,36 to our knowledge, the current study is the first to quantify how many osteopathic otolaryngology residents have a Emotional exhaustion, depersonalization, and personal accomplishment were scored as subscales on the Maslach Burnout Inventory-Human Services Survey. b The depersonalization and personal accomplishment subscales could not be calculated for 1 respondent because of incomplete responses to some questions.…”
Section: Discussionmentioning
confidence: 58%
“…23,24,36 Most otolaryngology residents are not assigned an official mentor, and the vast majority find mentors without a formal assignment. 36 Gurgel et al 24 reported that up to 69% of otolaryngology residency programs lack assigned mentors and that 89% of residents surveyed reported that mentoring was important or critical to their training; they found a significant correlation between small program size and a lack of formal mentoring. Another study showed that nearly all orthopedic surgery residents surveyed thought mentoring should be part of residency, and there was a significant increase in satisfaction when these residents were allowed to select a mentor.…”
mentioning
confidence: 99%
“…Hsu and colleagues reported implementation of a formalized mentoring program for otolaryngology residents and noted that successful implementation was often limited by time restrictions of the resident and faculty member, by lack of structure, and by loose monitoring of the relationship. 6 Initial challenges with the IPTeC mentor program included insufficient communication between IPTeC participants and the committee regarding the frequency or content of mentor-mentee interactions. As a result, the committee implemented two liaison positions.…”
Section: Discussionmentioning
confidence: 99%
“…During residency, mentoring is viewed as beneficial for career planning, specialty selection, and most notably, the pursuit of academic careers [8,12-16]. However, prior studies indicate that a large proportion of residents lack mentors [13,15].…”
Section: Introductionmentioning
confidence: 99%